Athletes and Academic Performance: A Study of Athletes at an NCAA Division I Institution - Mayo, Ann M. (My University, 1986)
The academic records of the athletes at a major Division I program were examined for the academic year 1980-81. The athletes were categorized by sex, grant-in-aid status, race, and as participating in either a revenue or non-revenue sport. The study documents that female athletes perform well academically. White male athletes achieve at their predicted grade point average. However, the results indicate that there is a specific problem area within the athletic population, specifically, the black athletes participating in football and basketball. The black student-athlete is often less prepared and experiences more serious academic problems than the white student-athlete. There were no significant differences between full, partial, and no scholarship athletes.
Keywords: race; scholarships; academic performance